Implementation of Madrasah Self-Evaluation in Improving The Quality of Graduates At Mts Astoffaina, Deli Serdang District - Rabbirham; Siahaan, Amiruddin; Syaukani (Graduate Program Magister Manajemen Pendidikan, 2025)
This study investigates how the implementation of Madrasah Self-Evaluation (EDM) drives improvements in graduate quality at MTs Astoffaina, Biru-Biru Subdistrict, Deli Serdang Regency. Employing a descriptive qualitative approach, the research uncovers that EDM fosters significant gains in graduate outcomes by promoting active stakeholder involvement, ensuring data transparency, and supporting evidence-based planning. Despite persistent challenges—such as limited human resources and insufficient familiarity with EDM instruments—the process has proven instrumental in elevating educational standards. The findings highlight the transformative potential of EDM when supported by targeted training and robust institutional backing, underscoring its critical role in advancing educational quality and school accountability.